O trabalho de parto como fenômeno psicossomático - Lovo, Lígia Maria Albani (2009)
The expression psychosomatic has been very used, mainly as research field due to the connection between the medical and psychological sciences. In this work, we propose to study the theory of psychosomatics through the psychoanalytic lens applying to a life-generating context: the childbirth situation. So, changing the focus of the illness, we can comprehend that body manifestations during the childbirth process are intrinsically connected to unconscious drive of life and death. The sample for this study is comprised of 180 women in labor in a state hospital in the East Zone of Sao Paulo, mostly between 20 and 30 years old, in the first pregnancy; 90% of the births were normal and 75% of the women were together with someone of her choice. Obstetric data like weight, gestation age and others correspond of a low risk pregnancy. When we looked at the psychological characteristics of the women in the moment of childbirth, we verified that the raped women, in their vast majority, could be considered well mentalized, in other words, had mental stability to deal with the frustrations. Even with this condition, these women obtained the best obstetric results, as postulated by the French school of psychosomatics, confirming the theory that bad mentalization is a predisposition to somatization. The less experienced women in labor were the ones with more psychic resources, this let us conclude that the experience of a previous birth can lower the expectations, dreams and plans of a new birth. Thus, in this work we verified the importance of the oniric life as protection of the psychosomatics organization and consequently of the investment of the death drive in favor of the life drive